3(x-5)+8=-(2-x)-25

Simple and best practice solution for 3(x-5)+8=-(2-x)-25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-5)+8=-(2-x)-25 equation:


Simplifying
3(x + -5) + 8 = -1(2 + -1x) + -25

Reorder the terms:
3(-5 + x) + 8 = -1(2 + -1x) + -25
(-5 * 3 + x * 3) + 8 = -1(2 + -1x) + -25
(-15 + 3x) + 8 = -1(2 + -1x) + -25

Reorder the terms:
-15 + 8 + 3x = -1(2 + -1x) + -25

Combine like terms: -15 + 8 = -7
-7 + 3x = -1(2 + -1x) + -25
-7 + 3x = (2 * -1 + -1x * -1) + -25
-7 + 3x = (-2 + 1x) + -25

Reorder the terms:
-7 + 3x = -2 + -25 + 1x

Combine like terms: -2 + -25 = -27
-7 + 3x = -27 + 1x

Solving
-7 + 3x = -27 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-7 + 3x + -1x = -27 + 1x + -1x

Combine like terms: 3x + -1x = 2x
-7 + 2x = -27 + 1x + -1x

Combine like terms: 1x + -1x = 0
-7 + 2x = -27 + 0
-7 + 2x = -27

Add '7' to each side of the equation.
-7 + 7 + 2x = -27 + 7

Combine like terms: -7 + 7 = 0
0 + 2x = -27 + 7
2x = -27 + 7

Combine like terms: -27 + 7 = -20
2x = -20

Divide each side by '2'.
x = -10

Simplifying
x = -10

See similar equations:

| -2.1x=14 | | p^2+6p-41=0 | | 3x+12=7(2x-3) | | 10x+2x=10x | | 5sinx-4=since | | 2s+4s=2s | | X-1/10=x-9/2 | | w-8.1=6.4 | | 1982.596=2*3.14*8.2*8.2+2*3.14*8.2*h | | t*3-8=9 | | 2x^3-10x^2-71x-9=0 | | a*6+8=13 | | 4n+73=5 | | 4x+6=-54-8 | | 3y=15-x | | -77=-++55 | | =(3-2)X+2Y+2 | | y=3.40x+2.20 | | 2x-4=86 | | ln(2x)-ln(3)=5 | | 3x+17=11x+47 | | 6x+106=2x+108 | | -2n^2+9=-7n | | =X+2Y+2 | | n-13=86 | | a^2-6a=9 | | c-28=51 | | -2x^2=-2-3x | | 35/7=p | | 3b-4/2 | | -21=9a-15-3 | | 7=g/8 |

Equations solver categories